Método simplificado de avaliação de conforto térmico para ambientes ventilados naturalmente ou híbridos do INI-C: desempenho e limitações - Helder Gattoni Medeiros (2022)
The need to implement measures to mitigate the buildings electricity consumption in the country led to the creation of the RTQ-C in 2009. Although Brazil has many naturally ventilated buildings, the RTQ-C is strongly oriented towards buildings that have air-conditioned systems. In 2021, the Brazilian Government published an improvement to the RTQ-C, renaming it to INI-C which, among other changes, presents a simplified method for evaluating the percentage of hours in thermal comfort (PHOCt) for naturally ventilated spaces. In this research the aim is to analyze the applicability and possible limitations of this method, using UFMG’s buildings located in Pampulha campus as a case study. For this purpose, the possibility of applying the method in buildings of different geometries was evaluated and the results of this method was compared with results obtained through simulation with EnergyPlus software. The 82 buildings considered of interest for the study were divided into three groups according to the applicability of the method: 1) applicable, 2) applicable with adjustments, and 3) not applicable. It was observed that 16% of the buildings belong to group 1, 61% to group 2 and 23% to group 3. If limits of cover thermal transmittance and absorbance and variation between APP are also taken into account, only 1 building would meet the limits of the metamodel (1.2%). Buildings in group 1 had their PHOCt evaluated with results ranging between 53% and 97%, and the buildings with higher occupancy densities and smaller indoor spaces tended to have worst results and those with lower thermal roof transmittance tended to have the best results. In addition, the simplified method was applied with modifications in 3 buildings from group 2 and the results were compared with computer simulations. The percentage differences in the PHOCt ranged between 2% and 6%, which was considered a satisfactory result for the simplified method, even with the necessary adjustments. For now, the new method is considered capable of promoting a general assessment of natural ventilation solutions in buildings, but for that, acceptable adjustments in its input parameters must be evaluated to expand its application.